Transcription termination promotes splicing efficiency and fidelity in a compact genome - Keaton Barr; Kevin L. He; Andreas J. Krumbein; Guillaume F. Chanfreau (Proceedings of the National Academy of Sciences, 2025)
Splicing of terminal introns is coupled to 3′-end processing by cleavage and polyadenylation (CPA) in mammalian genes. Whether this functional coupling is universally conserved across eukaryotes is unclear. Here, we show using long read RNA sequencing in Saccharomyces cerevisiae that splicing inactivation does not result in widespread CPA impairment, and that inactivation of CPA has limited impact on splicing efficiency. The negative impact of CPA inactivation on splicing is mainly due to transcription termination defects that promote readthrough transcription, leading to splicing inhibition for downstream intron-containing genes. The deleterious effect of 5′ extensions on splicing is length-dependent and can be detected independently from CPA inactivation for endogenous or synthetic genes. Deficient termination can also promote usage of cryptic splice sites and long-range intergenic splicing events. These results argue against a broad coupling between splicing and CPA in S. cerevisiae but show that efficient CPA-mediated transcription termination is critical for splicing fidelity and efficiency in a compact genome.